Access, consumption and preferences for the bean-based flour Consumer survey data in Burundi - Katungi, Enid Mbabazi; Nduwarugira, Eric; Ntukamazina, Jean Nepomuscene; Niragira Sanctus; Asiimwe, Robert; Robert Fungo (2025)
The data were collected as part of M&E to learn about your uptake of processed bean products by consumers and draw perspectives on new bean-based products from research partners. The specific objectives were: 1) assess and consumption of nutrient dense food products promoted by the project; 2) evaluate the potential demand for processed bean-based products, 3) identify drivers of demand for processed bean-based products, 4) examine nutrition knowledge by acquired consumers and 5) analyse the marketing models to increase demand. The survey was hinged on the consumption patterns of processed products from six processors supported under the flagship project.